Toward the enrichment of dietary proanthocyanidins: In vitro investigation of their concentration‐dependent complexation with β‐casein. Issue 1 (10th November 2020) - Ben Abdallah, Rim; Bautista‐Ortin, Ana Belén; Reche, Juana; Ghazouani, Tesnime; Talbi, Wafa; Osete‐Alcaraz, Andrea; Gómez‐Plaza, Encarna; Fattouch, Sami
Abstract: Considering the proanthocyanidins' (PA) potential health effects, nutritional, and organoleptic properties, their structure should be carefully preserved during food technological processing. Particularly, their interaction with proteins, leading to complex formation, alters their functional performance. In this context, proanthocyanidins‐rich persimmon and pomegranate peels were used to investigate the effect of variable PA/β‐casein relative concentrations on their in vitro interaction. High‐Performance Liquid Chromatography coupled to Diode Array Detector (HPLC) analyses showed that, using 0.008, 0.017, 0.028, and 0.035 mg catechin equivalent (CE) per milliliter of PA in the reaction medium, the proanthocyanidin–β‐casein interaction's potencies varied, respectively, from 29.12% versus 27.70%, 37.64% versus 33.04%, 16.44% versus 44.60% to 15.96% versus 38.73% ( p  < .05) with regards to pomegranate versus persimmon peel starting material. Moreover, Size‐Exclusion Chromatography (SEC) technique confirmed those findings. From the technological point of view, the relative concentration of PA‐protein should be considered to manage their interaction, thus, saving the aliment nutritional values as well as sensorial traits, particularly, astringency and haze formation. Practical applications: From the technological point of view, this work shows how proanthocyanidin‐protein' relative concentration should be considered to manage their interaction, thus, saving the aliment nutritional values as well as sensorial traits, particularly, astringency and haze formation. The pick of appropriate concentrations will be assumed to enhance the proanthocyanidin content of beverages and foods, during natural product handling by diminishing their inevitable adsorption to proteins, and so, avoiding haze formation. Additionally, in winemaking, targeting the fitting concentrations can be extremely useful since that winemakers can apply proteins as fining agents which can bind tannins molecules and precipitate them out as sediments to have a softer and less tannic taste.